Allelic Variants of ARMC5 in Patients With Adrenal Incidentalomas and in Patients With Cushing's Syndrome Associated With Bilateral Adrenal Nodules - Mariani, Beatriz Marinho de Paula; Nishi, Mirian Yumie; Wanichi, Ingrid Quevedo; Brondani, Vania Balderrama; Lacombe, Amanda Meneses Ferreira; Charchar, Helaine; Pereira, Maria Adelaide Albergaria; Srougi, Victor; Tanno, Fabio Yoshiaki; Ceccato, Filippo; Regazzo, Daniela; Barbot, Mattia; et al. (Frontiers in Endocrinology, 2020)
Objective: Germline ARMC5 mutations are considered to be the main genetic cause of primary macronodular adrenal hyperplasia (PMAH). PMAH is associated with high variability of cortisol secretion caused from subclinical hypercortisolism to overt Cushing’s syndrome (CS), in general due to bilateral adrenal nodules and rarely could also be due to non-synchronic unilateral adrenal nodules. The frequency of adrenal incidentalomas (AI) associated with PMAH is unknown. This study evaluated germline allelic variants of ARMC5 in patients with bilateral and unilateral AI and in patients with overt CS associated with bilateral adrenal nodules. Methods: We performed a retrospective multicenter study involving 123 patients with AI (64 bilateral; 59 unilateral). We also analyzed 20 patients with ACTH pituitary independent overt CS associated with bilateral adrenal nodules. All patients underwent germline genotyping analysis of ARMC5; abdominal CT and were classified as normal, possible or autonomous cortisol secretion, according to the low doses of dexamethasone suppression test. Results: We identified only one pathogenic allelic variant among the patients with bilateral AI. We did not identify any pathogenic allelic variants of ARMC5 in patients with unilateral AI. Thirteen out of 20 patients (65%) with overt CS and bilateral adrenal nodules were carriers of pathogenic germline ARMC5 allelic variants, all previously described. The germline ARMC5 mutation was observed in only one patient with bilateral AI; it was associated with autonomous cortisol secretion and showed to be a familial form. Conclusion: The rarity of germline ARMC5 mutations in AI points to other molecular mechanisms involved in this common adrenal disorder and should be investigated. In contrast, patients with overt Cushing´s syndrome and bilateral adrenal nodules had the presence of ARMC5 mutations that were with high prevalence and similar to the literature. Therefore, we recommend the genetic analysis of ARMC5 for patients with established Cushing´s syndrome and bilateral adrenal nodules rather than patients with unilateral AI.